Application of water quality biological indices using diatoms as bioindicators in the Gravataí river, RS, Brazil - Salomoni,SE. (2011)
The Gravataí river situated in the metropolitan region of Porto Alegre has an area of approximately 2.020 km² and provides public water supply to about 500,000 inhabitants in 5 municipalities (latitude 29° 45'-30° 12' S; longitude 50° 27'-51° 12' W). The river basin has two regions with distinctive characteristics of occupation: the upper course shows intensive farming and the lower course presents urban and industrial uses. In this context, the aim of this study was to evaluate the water quality in the Gravataí River (RS, Brazil) by using physical, chemical and microbiological variables, and the water quality biological indices (WQBI) formulated for southern Brazilian rivers based on epilithic diatom communities as indicators. For comparison purposes, a local WQBI, called the Gravataí WQBI, was also used where species were given new saprobic values (s) and indicative values (vi) according to their occurrence and abundance in the river, using multivariate analytical techniques. The biological samples were taken every three months at six stations along the Gravataí River between September 2000 and August 2002. The results of the physical and chemical analyses of the water indicated a pollution gradient down the river, from the headwaters to the mouth, detected mainly by considering a significant decrease in the concentration of dissolved oxygen and turbidity, as well as a significant increase in BOD5, total nitrogen, ortho-phosphate and thermotolerant coliforms. Comparing the results obtained, differences were found regarding the predominant pollution levels as higher in the Gravataí WQBI, although both corroborated a tendency for the contamination gradient to increase from the headwaters to the mouth. Given the local anthropic changes, it is of great importance to continue the study of diatom species tolerance to organic pollution and eutrophication in different lotic systems of the region.